Procedure For Providing Death Guarantee Insurance to Heirs Registered in BPJS Employment Sei Rampah Branch (Jurnal Begawan Hukum (JBH), 2024)
The implementation of providing death insurance to heirs is aimed at seeing how the procedures used by BPJS employment support the progress of social welfare..This research includes an analysis of the stages, requirements and obstacles faced by heirs in processing death insurance claims. The results of the research provide support for the sustainability of the death insurance program provided by the government, especially at the BPJS Employment Sei Rampah branch. The method used in this article is an empirical juridical research method using qualitative analysis.